(untitled) (Academia Journal of Medicine, 2025)
Distraction techniques play a vital role in managing anxiety and fear among pediatric dental patients. This scoping review aims to explore the various distraction methods used in pediatric dentistry, emphasizing their effectiveness and incorporation into clinical practice. The review encompasses a range of distraction strategies, including visual, auditory, and interactive approaches, to assess their impact on children’s emotional responses and cooperation during dental treatments. By synthesizing existing literature, the findings highlight the benefits of distraction in alleviating anxiety, improving patient experience, and enhancing treatment outcomes. The review also identifies gaps in current research and suggests directions for future studies to optimize the application of distraction techniques in pediatric dental settings.